Два новых сельских могильника в Подонцовье - Швецов, М.Л.; Санжаров, С.Н.; Прынь, А.В. (Степи Европы в эпоху средневековья, 2001)
The paper bears on new materials of the rural cemeteries on the left bank of the Seversky Donets river. The data obtained from the burials have enabled us to determine their chronology (the third quarter of the VIIIth century - the end of the Xth century) and to analyse their funeral rite features. Having correlated our data with those published earlier we could localize the cemeteries related to the neighbouring settlements, to specify their topography as to the land relief, climate conditions and economic activity of the population. The authors suggest that the burials layout (planigraphy) on each cemetery, their distinct parcelling into two sections (Chemikovo - Serebryanskoye, Dronovka -Platonovka. Novolymaryevka I and II) reflects not so much chronological or confessional differences, as kindred and social ones. The burials having some specific elements of the funeral rite (the prone position of the deceased), this adds to the knowledge of ihe character of the rural burial grounds in the Seversky Donets basin of Zlyvky type.